Exploration and Petrogenesis of Corundum-Bearing Pegmatites: A Case Study in Migif-Hafafit Area, Egypt - Khaleal, Farrage M.; Saleh, Gehad M.; Lasheen, El Saeed R.; Alzahrani, Abdullah M.; Kamh, Samir Z. (Frontiers in Earth Science, 2022)
A net of pegmatite veins crosscut gneiss and dismembered ophiolitic ultramafic rocks are abundant in Migif–Hafafit culmination area, South Eastern Desert, Egypt. Some of these pegmatites are corundum-bearing. Corundum-bearing pegmatites are, restricted to eight localities around Migif-Hafafit complex, distributed from north to south: Wadi El Qarn, Um Karaba, Um Maiat, Abu Merikhat, Um Nimr, north El Hima, south El Hima and Um Shegera areas. The present study aims to integrate field, corundum chemistry, remote sensing geological mapping approaches and the conventional methods to detect the corundum – bearing pegmatites and find out the genesis of the corundum mineralization as well. In addition, the tectonic regime has been detected using bulk rock geochemistry. FCCs, BR, PCA, MNF, DS and CEM image processing algorithms were proposed and applied on Landsat-8 and Sentinel-2A data to discriminate the exposed lithological units and to detect the corundum-bearing pegmatites in the study area. These detected pegmatites are structurally controlled following NW-SE direction. The studied pegmatites have both plumasite and marundite. Wadi El Qarn and Um Karaba host rocks are gneiss, whereas the ultramafic rocks are the host of other areas. Gneisses and pegmatites are characterized by steep slope of LREEs of relative to HREEs with week Eu negative anomaly. The studied pegmatites have both plumasite and marundite. On the other hand, the studied corundum has Al2O3 content up to 99.72 wt.% in pegmatite-gneiss and up to 100 wt.% in pegmatite-ultramafics. Corundum is ascribed to metamorphic/ metasomatic type according to its chromosphere. Desilication in pegmatites led to the excess of alumina content in the residual melt producing corundum mineralization.